1984
DOI: 10.2135/cropsci1984.0011183x002400020016x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of N Deposition to Grain Yield and N Response of Three Maize Hybrids1

Abstract: Three maize (Zea mays L.) hybrids were evaluated for their grain yield under different levels of spring‐applied anhydrous ammonia fertilizer. The N content in the vegetative tissues and grain was analyzed at the midsilk stage and at 60 days after pollination. Of the three hybrids tested, B14 ✕ Oh43 (intermediate type) responded to moderate levels of N fertility, B73 ✕ Mol7 (high‐fertility type) had a great response to additional N, and Pioneer 3732 (low‐fertility type) performed well under low levels of N fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 0 publications
2
45
1
Order By: Relevance
“…In an unreplicated trial, Tsai et al (1984) reported that Pioneer 3732with B73 x MolT pollen maintained a higher rate of biomass accumulation in the kernel, delayed physiological maturity, and increased kernel yield (20%) andkernel protein concentration, than when self-or sib-pollinated. In a replicated experiment over2 yr with these two hybrids, Tsai and Tsai (1990) In 1990, an attempt was also made to duplicate the unreplicated PM harvest published by Tsai et al (1984) (Tsai et al 1984;Tsai and Tsai 1990) was not found, nor was any increase in yield of the earliest maturing hybrid (Lx2) by pollen of the later maturing hybrids (Table 5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In an unreplicated trial, Tsai et al (1984) reported that Pioneer 3732with B73 x MolT pollen maintained a higher rate of biomass accumulation in the kernel, delayed physiological maturity, and increased kernel yield (20%) andkernel protein concentration, than when self-or sib-pollinated. In a replicated experiment over2 yr with these two hybrids, Tsai and Tsai (1990) In 1990, an attempt was also made to duplicate the unreplicated PM harvest published by Tsai et al (1984) (Tsai et al 1984;Tsai and Tsai 1990) was not found, nor was any increase in yield of the earliest maturing hybrid (Lx2) by pollen of the later maturing hybrids (Table 5).…”
mentioning
confidence: 99%
“…In a replicated experiment over2 yr with these two hybrids, Tsai and Tsai (1990) In 1990, an attempt was also made to duplicate the unreplicated PM harvest published by Tsai et al (1984) (Tsai et al 1984;Tsai and Tsai 1990) was not found, nor was any increase in yield of the earliest maturing hybrid (Lx2) by pollen of the later maturing hybrids (Table 5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ayoade (2011), drought is a major factor responsible for crop production and productivity decline in the temperate and tropical regions of the world. The use of drought-tolerant maize cultivars with high yielding potential to cope with the present climate change scenarios (Schittenhelm and Schroetter, 2014) is therefore important since access to drought-tolerant maize variety may be the only alternative mitigating option available to resource-poor African farmers (Tsai et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid variations in the percentage of final N taken up by the mid-silk stage may range from 40% to 100% (Hanway 1962 Our earlier studies indicate that maize hybrids grown in the Cornbelt may be grouped into three categories. They include: (1) low N-response hybrids which require a relatively small amount of N fertiliser to reach maximum yield potential, and (2) intermediate and (3) high N-responsive hybrids which respond to moderate and large amounts of N, respectively, for higher yield potentials (Tsai C Y et al 1984). Other workers have found little difference in the N requirement for maximum yield of different maize hybrids (Bundy and Carter 1988; Gardner et a1 1990); however, it is not clear whether suppressive environments for high yield, high residual soil N, or a combination of both might account for the differences observed.…”
Section: Introductionmentioning
confidence: 99%